2005
DOI: 10.1128/iai.73.8.4834-4845.2005
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression and the Role of Sigma Factors in Neisseria gonorrhoeae in Interactions with Epithelial Cells

Abstract: Like many bacterial pathogens, Neisseria gonorrhoeae must adapt to environmental changes in order to successfully colonize and proliferate in a new host. Modulation of gene expression in response to environmental signals is an efficient mechanism used by bacteria to achieve this goal. Using DNA microarrays and a tissue culture model for gonococcal infection, we examined global changes in gene expression in N. gonorrhoeae in response to adherence to host cells. Among those genes induced upon adherence to human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
50
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 81 publications
(85 reference statements)
7
50
2
1
Order By: Relevance
“…In addition, when comparing the transcriptional profiles of RNA samples isolated before and after incubation in saponin, we found that these incubation conditions caused no appreciable change in bacterial gene expression (expression of ϳ0.1% of all genes changed by a statistically significant measure [data not shown]). This is consistent with studies of other bacterial pathogens, where saponin has also been used to specifically lyse host cells and has been shown to have no noticeable effect on bacterial gene expression (18).…”
supporting
confidence: 77%
“…In addition, when comparing the transcriptional profiles of RNA samples isolated before and after incubation in saponin, we found that these incubation conditions caused no appreciable change in bacterial gene expression (expression of ϳ0.1% of all genes changed by a statistically significant measure [data not shown]). This is consistent with studies of other bacterial pathogens, where saponin has also been used to specifically lyse host cells and has been shown to have no noticeable effect on bacterial gene expression (18).…”
supporting
confidence: 77%
“…In particular, we noted that expression of rpoH, which encodes the stress-related sigma factor RpoH, and some RpoH-regulated genes (grpE, clpB, and marR [8,29]) were increased in strain JF1 relative to the MtrR-positive parental strain FA19, suggesting that they are MtrR repressed. Since RpoH expression in gonococci is increased during exposure to certain environmental stresses (8) when gonococci bind to cervical epithelial cells (2,3) and is essential for viability (3,8), we studied the ability of MtrR to regulate rpoH expression in N. gonorrhoeae.…”
Section: Resultsmentioning
confidence: 99%
“…H 2 O 2 assays were performed because loss of RpoH production was found to enhance the susceptibility of Brucella melitensis (1) to the oxidizing agent. Since we (unpublished observations) and others (3,8,14) have been unsuccessful in obtaining an rpoH null mutant, we hypothesized that under conditions where rpoH expression is dampened due to the repressive action of MtrR, gonococcal susceptibility to H 2 O 2 would increase. Indeed, we found that inducible expression of mtrR increased gonococcal susceptibility to H 2 O 2 (Fig.…”
Section: Vol 191 2009mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been proposed that the intestine is relatively nutrient poor (28), and some of the 32 -regulated genes listed in Table 2 may promote growth under nutrientlimiting conditions. Adherence of V. cholerae to the intestinal epithelium may promote 32 activation, as has been observed following adherence of Neisseria gonorrhoeae to host epithelial cells (11). Adherence could stimulate changes in the cell membrane that activate E , which appears to be a regulator of rpoH in V. cholerae.…”
Section: Discussionmentioning
confidence: 99%